Mobile Video Streaming Applications: A Systematic Review of Test Metrics in Usability Evaluation - Hussain, Azham; Mkpojiogu, Emmanuel O.C; Mohmad Kamal, Fazillah (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
In evaluating the usability of mobile video streaming applications, the performance of the applications comes into focus. This is because the performance of mobile streaming applications affects their usability. From this study, video streaming and video quality are identified as the two most evaluated elements in the usability test of mobile video streaming applications. These elements are affected by several related factors that are peculiar to the mobile platforms and domains. These in turn affect the usability of the applications. In mobile platforms, bandwidth is low and network connections are unstable; this is coupled with the limitations caused by the smallness of the screen sizes of the mobile devices. Furthermore, startup delays, jitter, latency and rebuffering are the determining factors for the performance of mobile video streaming. On the other hand, video quality is determined by frame rate, bit rate, and resolution. These factors present themselves due to the mobile context of mobile streaming applications. They combine to influence the performance of the applications as well as their usability. Therefore, in considering the usability of these set of applications, these factors (metrics) are important as they determine the performance of the applications and by and large also affect the usability of the applications. Other factors identified in the study that affect the usability of mobile streaming applications include: functionality, social context and user interface and appearance. On the whole, this paper presents the results of a systematic review of test metrics in the usability evaluation of mobile video streaming applications. The systematic review approach used include: defining the search strategy, selection of primary studies, the extraction of data, and the implementation of a synthesis strategy. Using this methodology, 238 studies were found; however, only 51 relevant studies were eventually selected for the review. The study reveals that time taken for video streaming and the video quality were the two most popular metrics used in the usability test and evaluation of mobile video streaming applications. Besides, most of the studies concentrated on the usability of mobile TV as users switch from traditional TV to mobile TV.